STUDENTS’ SPEAKING ENGLISH DIFFICULTIES BASED ON GENDER AT SMP IT AN-NIDA’ LUBUKLINGGAU - Stefani, Nabila; Triyogo, Agus; yulfi (Lingustic, Literature and English Education, 2023)
This research aimed (1) to find out the difficulty of speaking English based on gender at SMP IT An-Nida' Lubuklinggau and (2) to find out the causes of difficulty speaking English based on gender at SMP IT An-Nida' Lubuklinggau. This research used the qualitative descriptive method. The subjects in this study were classes VIII.1 and VIII.2 with the purposive sampling technique. Data collection techniques include questionnaires and interviews. In data analysis techniques, researchers use three steps: 1) data reduction, 2) data display, and 3) conclusion. The results of this research showed that most of the respondents experienced difficulties speaking English. (1) difficulties in pronunciation, lack of grammar, difficulty to memorize vocabulary, and their English is not very fluent. (2) Furthermore, the causes of students' difficulties from the research are lack of confidence, anxiety, fear of speaking, embarrassment to speak in front of the class, fear of speaking English incorrectly, and fear of making mistakes. difficulties in speaking English based on gender (1) Most females have difficulties in pronunciation, while (2) males have difficulties in grammar and vocabulary. From the results of the questionnaires, the scores of female students were 14,28% while the score of male students 66,66% of students had difficulty speaking English.. This indicates that male students are more difficult to speak English than female students.